Immunomodulatory Effects and Mechanisms of Curcuma Species and Their Bioactive Compounds: A Review - Yuandani,; Jantan, Ibrahim; Rohani, Ade Sri; Sumantri, Imam Bagus (Frontiers in Pharmacology, 2021)
Curcuma species (family; Zingiberaceae) are widely utilized in traditional medicine to treat diverse immune-related disorders. There have been many scientific studies on their immunomodulating effects to support their ethnopharmacological uses. In this review, the efficacy of six Curcuma species, namely C. longa L., C. zanthorrhiza Roxb., C. mangga Valeton & Zijp, C. aeruginosa Roxb., C. zedoaria (Christm.) Roscoe and C. amada Roxb. and their bioactive metabolites to modulate the immune system, their mechanistic effects and their potential to be developed into effective and safe immunomodulatory agents are highlighted. Literature search has been carried out extensively to gather significant findings on immunomodulating activities of these plants. The immunomodulatory effects of Curcuma species were critically analyzed and future research strategies and appropriate perspectives on the plants as source of new immunomodulators were discussed. Most of the pharmacological investigations to evaluate their immunomodulatory effects were in vivo and in vitro experiments on the crude extracts of the plants. The extracts were not chemically characterized or standardized. Of all the Curcuma species investigated, the immunomodulatory effects of C. longa were the most studied. Most of the bioactive metabolites responsible for the immunomodulating activities were not determined, and mechanistic studies to understand the underlying mechanisms were scanty. There are limited clinical studies to confirm their efficacy in human. Of all the bioactive metabolites, only curcumin is undergoing extensive clinical trials based on its anti-inflammatory properties and main use as an adjuvant for the treatment of cancer. More in-depth studies to understand the underlying mechanisms using experimental in vivo animal models of immune-related disorders and elaborate bioavailability, preclinical pharmacokinetics and toxicity studies are required before clinical trials can be pursued for development into immunomodulatory agents.